STRENGTHENING CULINARY FISH PRODUCTION IN LAUK BABAKAN VILLAGE, BOGOR CITY - Batubara, Rima Pratiwi; Setiawan, Aditya Sugih; Sari, Dhanik Puspita (LPPM Univ. Ibn Khaldun Bogor, 2024)
Lauk Babakan Village is one of the tourist villages in Bogor City. Previous research revealed that the community, especially women around Lauk Babakan Village, had conducted workshops on making fish dishes to support tourism activities in the local area. The food products made are shredded catfish and catfish nuggets. The community also has other food businesses such as ready-to-fry seasoned fish, fish fillets and others. The problem with partner groups is that there are fewer people who are active in trying and working together to support local tourism activities. The aim of this activity is to revive community interest and participation in producing fish-based culinary delights in accordance with the superior potential of the local area. This activity also makes it easier for local people who want to try their hand at the culinary sector by providing packaging for local culinary production. Implementation activities result in participants who have taken part in fish culinary training being able to produce fish culinary dishes correctly. Fish culinary products made by the community have been marketed through social media and exhibitions.